INKLUSI INTEGRATION OF SOCIAL-EMOTIONAL LEARNING IN A HAPPY SCHOOL: A CASE STUDY OF AN INCLUSION CLASS - umin; Indana Zulfa Majidah; Muhammad Mukhlis Roziqi; Anas Ahmadi; Agus Harminto (Universitas Negeri Semarang, 2024)
Abstrak This study examines the integration of Social Emotional Learning (SEL) in the inclusive education program at SMP Negeri 40 Surabaya. The research aims to integrate social-emotional learning within the school well-being framework and to understand how the inclusive classrooms at SMP Negeri 40 Surabaya incorporate social-emotional learning into inclusive education. This research uses a qualitative case study method to apply SEL to support inclusive student interaction and emotional well-being. The study results indicate that SMP Negeri 40 Surabaya has made significant strides toward creating an inclusive and supportive learning environment by implementing an accommodating curriculum, support from special assistant teachers, and an adaptive assessment system. Although challenges such as resource needs and teacher training remain, integrating SEL has positively impacted the inclusive learning environment. This study emphasizes the importance of sustained commitment to resource development and training to optimize SEL in inclusive education.